2016
DOI: 10.1038/srep19075
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies three key loci for high mesocarp oil content in perennial crop oil palm

Abstract: GWAS in out-crossing perennial crops is typically limited by insufficient marker density to account for population diversity and effects of population structure resulting in high false positive rates. The perennial crop oil palm is the most productive oil crop. We performed GWAS for oil-to-dry-mesocarp content (O/DM) on 2,045 genotyped tenera palms using 200K SNPs that were selected based on the short-range linkage disequilibrium distance, which is inherent with long breeding cycles and heterogeneous breeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…For each of the traits, a genome-wide association study (GWAS), using the same method as described in our previous publication 38 , was carried out independently for each iteration during the cross validation step. Markers were ranked according to the association score.…”
Section: Methodsmentioning
confidence: 99%
“…For each of the traits, a genome-wide association study (GWAS), using the same method as described in our previous publication 38 , was carried out independently for each iteration during the cross validation step. Markers were ranked according to the association score.…”
Section: Methodsmentioning
confidence: 99%
“…But in oil palm association mapping may offer a valuable technology to identify the genetic loci of important traits. The CK et al [2] performed GWAS for oil-to-dry-mesocarp content on 2045 genotyped tenera palms using 200K SNPs and found that 80 loci were significantly associated with oil-to-dry mesocarp yield (P ≤ 10-4), and three key signals were found. In oil palm, vegetative propagation is made possible only via tissue culture.…”
Section: Editorialmentioning
confidence: 99%
“…GWAS, QTL and association mapping studies have been increasingly reported for oil palm breeding, particularly for oil content [115][116][117][118][119][120]. Bai et al [116] showed that by combining QTLs with beneficial genotypes, the resulting average oil content in fruit bunches was higher.…”
Section: Oil Palm Omics Research Related To Yieldmentioning
confidence: 99%
“…Kwong et al [117] developed a SNP array for oil palm using various origins. This platform was particularly useful for developing early trait prediction methods to shorten the oil palm breeding cycle and was used to identify QTL loci for important oil content traits [115]. Informative QTLs linked to oil yield component traits were also mapped in a high-yield population [118].…”
Section: Oil Palm Omics Research Related To Yieldmentioning
confidence: 99%
See 1 more Smart Citation